Nancy Drew. The final season [videorecording (DVD)] - Landau, Noga; Schwartz, Josh, 1976-; Savage, Stephanie (Paramount, 2023)
The final season begins as Nancy launches a new investigation to find a group of missing bodies from Horseshoe Bay's cemetery that have been dug up and stolen or have possibly risen. As Nancy is drawn into this ghostly case, a string of unexplained paranormal crimes leads the Drew Crew to believe that the literal sins of the town's past have returned to haunt the living.